2016
DOI: 10.1118/1.4959539
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Robust measurement of the slice-sensitivity profile in breast tomosynthesis

Abstract: Measuring the SSP in the volumes in a CBCS improves the robustness of the measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The FWHM is used to quantify the width of the profile ( van Engen et al 2018). The influence of the geometry and reconstruction coordinate system on the ASF is examined in the study of Maki et al (2016). Two approaches are generally adopted by the vendors.…”
Section: Artefact Spread and Resolution In The Z-directionmentioning
confidence: 99%
“…The FWHM is used to quantify the width of the profile ( van Engen et al 2018). The influence of the geometry and reconstruction coordinate system on the ASF is examined in the study of Maki et al (2016). Two approaches are generally adopted by the vendors.…”
Section: Artefact Spread and Resolution In The Z-directionmentioning
confidence: 99%
“…In addition to the viewing benefits of conical‐grid reconstruction volumes (no relative movement of objects between slices), the small variation in MTF( x ) across the volume means that shift‐variance is close to negligible in this direction and thus MTF measurements should generally be more robust in a conical reconstruction grid than in a Cartesian reconstruction grid, that is, one can expect a simplified analysis and measurements being less sensitive to position and ROI size. Similarly, it has previously been found that measurements of height resolution in a conical reconstruction grid are more robust than measurements in a Cartesian reconstruction grid . This robustness does, however, not apply for the y direction, which exhibits a large variation in MTF across the volume.…”
Section: Discussionmentioning
confidence: 99%
“…The system uses a conical reconstruction grid, that is, a voxel grid that is aligned to the rays of the central projection. For flat‐panel systems, the corresponding grid is also known as a cone‐beam coordinate system . The conical reconstruction grid results in a voxel size that varies throughout the volume, shown in the top of Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations